Sub-surface Geological Modeling Based on Gravity Residual Data in Adang Volcanic Rock Area, Mamuju, West Sulawesi Province - Karunianto, Adhika Junara; Haryanto, Dwi; Ngadenin (BRIN Publishing, 2022)
The Mamuju area of West Sulawesi Province is composed of Adang volcanic rock that is a product of the process of volcanism in a volcanic complex with an eruption center and several lava domes. The geology of the study area is composed of eleven rock units, namely Adang breccia, Adang lava, lava dome, volcanic conglomerate, Ampalas breccia, Malunda breccia, Boteng lava, Tapalang breccia, limestone, reef limestone, and alluvium. The mineralization of uranium, thorium, and rare earth elements formed in Adang lava thorianite veins. Adang lava is intruded by a dioritoid found in the Mamuju river upstream. The gravity modeling technique has produced two 2-D subsurface models based on gravity data on 2-D cross-sections of the residual gravity map. It is known that the rock density range from 2.10 to 2.85 g/cm3 in the study area. Based on the interpretation of two 2-D subsurface models, a batholith, a giant-sized intrusive rock, is found in the southeastern part of the study area with a rock density of about 2.85 g/cm3 and is interpreted to be dioritoids. Furthermore, deep intrusion rocks also occur in the center part of the study area with a rock density of 2.8 g/cm3. It is estimated to be the same as the rock in the southeastern part of the study area. Dioritoid intrudes a volcanic breccia sedimentary rock with a density of about 2.1 g/cm3.